Results of introduction of ligneous lianas in the SE EF “Novokakhovskoye” (Nikitsky Botanical Garden–National Scientific Center) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The results of introduction of 18 species and 4 hybrid of ligneous lianas are discussed with special emphasis to their overwintering in season 2005-2006.
Keywords: introduction, damage, temperature.